The Subjective Mental Well-Being of School-Age Children – Educational and Prophylactic Challenges - Zadworna-Cieślak, Magdalena; Kossakowska, Karolina (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The World Health Organization (WHO) regards the concept of health as individual psychosocial well-being based not only on physical, but psychological, social and environmental factors. Due to the long time spend at school, that context exerts a strong influence on the well-being of children and adolescents and plays an important role in their physical and mental health. Good mental condition in childhood and adolescence is a prerequisite for optimal development, effective learning, the formation of satisfying interpersonal relationships, and for maintaining physical and mental health in adult life. The aim of this paper is to describe the concept of socio-psychological well-being at school and major factors that influence it. Research about well-being of Polish adolescents will also be reviewed. Some preventive and educational implications will be drawn. Childhood and adolescence are crucial periods for the promotion of mental health and the prevention of mental disorders. The article is based on the assumption that the school environment is one of the key elements affecting the subjective psychological well-being of pupils. The school context is also necessary for taking appropriate preventive action and support school-age children in developing appropriate competences.